One Health Economics approach to prevention and control of zoonotic and animal diseases - considerations for South Africa - Manana Mamabolo; Catherine Machalaba; Siphe Zantsi; Melinda K. Rostal; William B. Karesh; Peter Neil Thompson; Petronella Chaminuka (One Health Outlook)
Abstract Outbreaks of animal and zoonotic diseases in South Africa are costly and raise concerns about national biosecurity. The interconnectedness of humans, livestock, wildlife and their social and ecological environment necessitates a holistic approach to prevention, preparedness and response to zoonotic and animal diseases. One Health is an increasingly accepted approach in contemporary science and policy spheres, but with limited consideration for economic dimensions. To more fully estimate costs of animal and zoonotic diseases in the country and to explore further scope for applying a One Health economics lens, the Agricultural Research Council of South Africa, in collaboration with partners, held a One Health Economics mini-congress to provide a platform where multidisciplinary stakeholders discussed practical examples, primarily from the Southern African region. Discussions at the mini-congress centred around One Health economics and opportunities, economic insights on prevention and control of Rift Valley fever (RVF), avian influenza and other zoonotic diseases, return on investment for One Health approaches, and insights from the natural resources and animal and human health sectors. Regional and international perspectives on multi-sectoral economic analysis and financing were also shared. Key recommendations from the mini-congress included promoting coordination, co-creation and co-implemented efforts to minimize effects of One Health challenges, and including economic aspects of multi-sectoral engagement to identify and reduce trade-offs and maximize co-benefits of strategies and programmes. Integration of economics in One Health fora, research and collaboration, and promotion of communities of practice and applied training to enhance learning and knowledge exchange were also identified as important.